Children and Parents Deserve Better Parental Discipline Research: Critiquing the Evidence for Exclusively "Positive" Parenting. Issue 1 (2nd January 2017) - Larzelere, Robert E.; Gunnoe, Marjorie Lindner; Roberts, Mark W.; Ferguson, Christopher J.
ABSTRACT: This article critiques the scientific evidence for the emerging view in nonclinical parenting research and in popular books that parents should use only positive methods of parenting and rarely resort to any disciplinary consequences. Four methodological fallacies pervade research used to support this viewpoint: the correlational fallacy (inferring causation from correlations), the trumping fallacy (permitting correlational conclusions to trump stronger causal evidence), the extrapolation fallacy (extrapolating favorable comparisons of under-usage versus over-usage to zero usage), and the lumping fallacy (lumping inappropriate and appropriate usages together). Conclusions based on any of these methodological fallacies are premature at best and counterproductive at worst. These fallacies would incorrectly make many medical procedures appear to be harmful, such as radiation treatment. Premature conclusions supporting exclusively positive parenting may partially explain the immigrant paradox in the United States and escalating criminal assaults against minors according to Swedish criminal records (where positive parenting is most prominently advocated). Exclusively positive parenting needs to be supported by stronger research, including randomized trials with oppositional defiant children, before being accepted as definitive. We also need research to understand how the parental management skills featured in effective clinical treatments for young oppositional defiant children generalize to parenting in nonclinical families.